Pengaruh VAP Bundle Intervention Dalam Pencegahan VAP Pada Pasien Terpasang Ventilator Mekanik Di Ruangan ICU RSUD Prof. Dr. H. Aloei Saboe Kota Gorontalo - Damasnyah, Haslinda; Yunus, Pipin; Monoarfa, Susanti; Taliki, Verawaty (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Patients who are on a mechanical ventilator can increase the risk of nosocomial infections because this is a potential complication that can occur, including patients experiencing Ventilator Associated Pneumonia (VAP). The aim of this study was to analyze the effect of VAP bundle intervention in preventing VAP in patients on mechanical ventilators in the ICU Room at Prof. Hospital. Dr. H. Aloei Saboe Gorontalo City. Methods: The research method used is pre-experimental research with one group pre-post test design to carry out CPIS (Clinical Pulmonary Infection Score) measurements to diagnose VAP. Results: The results of this study were obtained before the VAP bundle intervention in patients on mechanical ventilators in the ICU, the average CPIS score was 4.75. After the VAP bundle intervention, the patient was placed on a mechanical ventilator in the ICU Room at Prof. Hospital. Dr. H. Aloei Saboe, Gorontalo City, the average CPIS score is 3.42. The results of the Wilcoxon statistical test obtained a p-value of 0.001 (<α 0.05), meaning that there is an influence of VAP bundle intervention in preventing VAP in patients on mechanical ventilators in the ICU room at the Regional Hospital Prof. Dr. H. Aloei Saboe Gorontalo City. Conclusion: From this research data, the implementation of VAP prevention measures and the patient's disease condition is supported by the provision of pharmacological therapy according to the dose.Elevation of the head 30-45° can reduce the occurrence of oropharyngeal and gastrointestinal aspiration and increase the patient's lung volume and lung ventilation. Oral hygiene with antiseptic chlorhexidine 0.02% as an inhibitor of dental plaque formation and gingivitis.